Theoretical Study on Molecular Structure and Electronic Properties of New 1,3-Diaza-adamantan-6-ones Derivatives - Haithem Abdulhasan; Ahmed Al-Yasari; Rahman Alasadi (Indonesian Journal of Chemistry, 2020)
In this study, the structural geometry and vibrational frequencies (IR) of 1,3-Diaza-adamantane-6-ones derivatives including Adamantane (A), 1,3-Diaza-adamantan (D), 1,3-Diaza-adamantan-6-one (DO), 5-Benzyl-1,3-diaza-adamantan-6-one (BD), 5-(4-Hydroxybenzyl)-1,3-diaza-adamantan-6-one (HBD), 5-(4-Methoxybenzyl)-1,3-diaza-adamantan-6-one (MBD), and 5-(4-Hydroxy-3-methoxybenzyl)-1,3-diaza-adamantan-6-one (HMBD) were theoretically studied. In addition, molecular orbital energies, including the highest occupied molecular orbitals (HOMOs), and lowest unoccupied molecular orbitals (LUMOs), and electronic properties of the titled molecules were theoretically studied using the computational method. Optimized molecular structures were obtained by DFT method with the hybrid B3LYP functional at a relatively small basis set of 6-31G. The calculated vibrational wavenumbers were obtained using the same level of the theory mentioned above. The contributions to the molecular orbitals of adamantane and substituted-phenyl groups in the title compounds were determined. Moving from A to HMBD, a decrease in the value of LUMO and total energy are noticed, while an increase in the value of HOMO is noted. These findings are supported by the decreasing in the EHOMO-LUMO gap values. Furthermore, a decrease in the value of ionization potential (IP) is obtained, while an increase in the electronegativity (EA) is observed.